To determine if \( x = -3 \) is a solution to the quadratic equation \( -3x^2 - 9x = 0 \), we can substitute \( x = -3 \) into the equation and simplify.
Substituting \( x = -3 \):
\[ -3(-3)^2 - 9(-3) = 0 \]
Now, calculate each term:
-
Calculate \( (-3)^2 \): \[ (-3)^2 = 9 \]
-
Now substitute that back into the equation: \[ -3(9) - 9(-3) = 0 \]
-
Now calculate: \[ -27 + 27 = 0 \]
So, we have: \[ 0 = 0 \]
This indicates that when substituting \( x = -3 \) into the equation, it results in a true statement.
Therefore, the correct conclusion is:
Yes, \( x = -3 \) is a solution to the quadratic equation \( -3x^2 - 9x = 0 \) because substituting it back into the equation results in the equation holding true:
\[ -27 + 27 = 0 \]
Let me know if you need further assistance!